Zinc oxide nanoparticles to increase yield, bioactive compounds and enzyme activity in lettuce - Fortis-Hernández, Manuel; Pivaral-Chávez, Alexis GabrieL; Galindo-Guzmán, Alma Patricia; Preciado-Rangel, Pablo; Ruiz-Ortega, Francisco Javier; Trejo-Valencia, Radamés (Ecosistemas y Recursos Agropecuarios, 2024)
Zinc deficiency as a micronutrient reduces crop yields and as a trace element in humans affects immune and cognitive functions in susceptible individual. It is necessary to supply Zn to plants so that they can complete their life cycle and provide important levels of this element in food. Nanotechnology, involves the foliar application of nanoparticles that, due to their size, are easily penetrated and act as elicitors or biostimulants to improve plant metabolism and defense. In the present work, the effect of foliar application of NPs-ZnO on the yield, bioactive compounds and enzymatic activity of lettuce in hydroponics was evaluated. Five treatments were evaluated: control, 10, 20, 30 and 40 mg L-1. The results show a positive effect on yield and bioactive compounds, where the treatments with the NPs-ZnO outperformed the control treatment. The highest activity of the catalase and peroxidase enzymes, compared to the control, was obtained with the highest dose and the highest concentration of Zn in the lettuce leaves was obtained with the Nps treatments, exceeding the control treatment by 39% more. The foliar application of NPs-ZnO improves the production of orejona lettuce, showing greater yield, quality in bioactive and enzymatic compounds, also increasing the Zn content, thereby achieving the contribution of this trace element to the consumer.Keywords: Lactuca sativa, DPPH+, hydroponics, catalase, peroxidase.
Keywords: Láctica sativa; DPPH radical; Hydroponics; Catalase; Peroxidase